A decade of DesignSafe: enabling open science in natural hazards - Rathje, Ellen M.; Kumar, Krishna; Esteva, Maria; Brandenberg, Scott J.; Cockerill, Tim; Dawson, Clint; Padgett, Jamie E.; Pinelli, Jean-Paul; Stanzione, Dan (Frontiers in Built Environment, 2025)
DesignSafe (www.designsafe-ci.org) is the leading cyberinfrastructure for engineering and social science research related to natural hazards. It provides tools for managing, analyzing, and sharing data, helping researchers study how natural hazards affect both physical infrastructure and communities. DesignSafe connects curated datasets from academic experimental facilities and field reconnaissance teams to researchers focused on data analysis, computation, and numerical simulation. The platform provides researchers with petabyte-scale storage and hundreds of millions of computing hours mediated by intuitive interfaces that lower the bar of entry to advanced computational capabilities. By enabling sophisticated simulations and data-driven workflows previously unattainable with desktop computers or small clusters/servers and enabling streamlined data curation, publication, and dissemination, DesignSafe empowers researchers to accelerate discoveries and helps them amplify the impact of their work.